DINAMIKA N-NH4 DAN N-NO3 AKIBAT PEMBERIAN PUPUK UREA DAN KAPUR CaCO3 PADA TANAH INCEPTISOL KWALA BEKALA DAN KAITANNYA TERHADAP PERTUMBUHAN TANAMAN JAGUNG - Abdul Rasyid B Damanik; Hamidah Hanum; Sarifuddin Sarifuddin (Jurnal Agroekoteknologi, 2014)
The objective of this research were to determine the effect of urea fertilizer and lime-CaCO3applications and its interaction on the dynamics of N-NH4 and N-NO3 and changes in soil pH andgrowth of maize in Inceptisols taken from Kwala Bekala. This research was conducted in thegreenhouse, Chemistry and Soil Fertility Laboratory, at the Faculty of Agriculture, University ofNorth Sumatra, Medan. This study used a randomized block design (RBD) factorial consisting oftwo factors. The first factor was urea (U) which was composed of doses 0, 75, 150 and 225 kg N/haand the second factor was lime-CaCO3 (K) which was composed of doses 0, 2.032, 4.064, 6.096tons CaCO3/ha. The results showed that the application of urea fertilizer, lime-CaCO3 andinteractions increased N-NH4 in the first week and then decreased until the sixth week andincreased the N-NO3 until the fifth week and raised the soil pH in the first and second week thendecreased until the sixth week. The applications of doses urea fertilizer decreased plant height, stemdiameter, shoot dry weight and root dry weight. The application of lime-CaCO3 decreased thegrowth of the maize except the concentration of plant nitrogen. The interaction of urea fertilizer andlime-CaCO3 decreased stem diameter and shoot dry weight.Keywords : Inceptisols, Urea Fertilizer, Lime CaCO3, N-NH4 and N-NO3